2006
DOI: 10.1051/0004-6361:20065408
|View full text |Cite
|
Sign up to set email alerts
|

Direct constraint on the distance of γ2 Velorum from AMBER/VLTI observations

Abstract: Context. Interferometry can provide spatially resolved observations of massive star binary systems and their colliding winds, which thus far have been studied mostly with spatially unresolved observations. Aims. We present the first AMBER/VLTI observations, taken at orbital phase 0.32, of the Wolf-Rayet and O (WR+O) star binary system γ 2 Velorum and use the interferometric observables to constrain its properties. Methods. The AMBER/VLTI instrument was used with the telescopes UT2, UT3, and UT4 on baselines ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 28 publications
3
59
1
Order By: Relevance
“…Baselines ranging from 100 m to 300 m are mandatory to provide a detectable effect that could be measured accurately for the closest WR stars. SUSI ) and the VLTI (Glindemann et al 2004) have already carried out pioneering works in this field (North et al 2007;Millour et al 2007). …”
Section: Circumstellar Environmentsmentioning
confidence: 99%
“…Baselines ranging from 100 m to 300 m are mandatory to provide a detectable effect that could be measured accurately for the closest WR stars. SUSI ) and the VLTI (Glindemann et al 2004) have already carried out pioneering works in this field (North et al 2007;Millour et al 2007). …”
Section: Circumstellar Environmentsmentioning
confidence: 99%
“…This system was observed by Millour et al (2007) with the VLTI/AMBER and by North et al (2007) with the SUSI interferometer. Millour et al (2007) using a relatively restrained data set have set tight constraints on the geometrical parameters of the γ 2 Velorum orbit.…”
Section: γ 2 Velmentioning
confidence: 97%
“…This system was observed by Millour et al (2007) with the VLTI/AMBER and by North et al (2007) with the SUSI interferometer. Millour et al (2007) using a relatively restrained data set have set tight constraints on the geometrical parameters of the γ 2 Velorum orbit. A nice example of the constraints brought by interferometry is the work done by Millour et al (2007) where they have drastically reduced the error box derived from the classical radial velocity method by using an interferometric fit to retrieve the geometrical parameters of the binary star.…”
Section: γ 2 Velmentioning
confidence: 97%
See 1 more Smart Citation
“…a spiral-like pattern tracing the orbital motion of the wind-collision layer. The first Wolf-Rayet stars observed with long-baseline optical interferometry were γ 2 Vel (Millour et al 2007) and WR 118 (Millour et al 2009b). In both papers, the authors manage to resolve the system, and in that second one, they found closure phase signal compatible with a pinwheel model.…”
Section: The Multiplicity Of Massive Starsmentioning
confidence: 98%